Evaluation of Fish Communities in Daya Bay Using Biomass Size Spectrum and ABC Curve - Xu, Shannan; Guo, Jianzhong; Liu, Yong; Fan, Jiangtao; Xiao, Yayuan; Xu, Youwei; Li, Chunhou; Barati, Bahram (Frontiers in Environmental Science, 2021)
Based on the data collected by four trawl surveys during 2016–2017, we applied biomass size spectrum (BSS) and abundance–biomass comparison (ABC) curve to assess the status of fish communities’ status in Daya Bay, China. Our findings indicated a unimodal pattern and biomass size ranged from −2 to 10 grain levels and the pattern of the Sheldon-type BSS of fish in Daya Bay. Moreover, fishes in the range of four to eight size class were relatively abundant. The highest peak belonged to the two to four grain level (log2 size bins), mainly consisting of Leiognathus brevirostris, Callionymus meridionalis, Callionymus koreanus, Evynnis cardinalis, Trachurus japonicus, and other small fishes. The curves of the BSS in spring and winter were relatively flat and comprised a large curvature. The summer and autumn curves were comparatively steep, and the seasonal curvature was small. The curvatures of the curve were mainly related to a large number of small Evynnis cardinalis and a small number of large-sized Harpadon nehereus and Leiognathus ruconius. In our study, it was observed that the number and the size of the breeding population, trophic levels, migration habits, and other life history characteristics, as well as anthropogenic disturbances (especially overfishing), significantly affected the peak shape, slope, or curvature of the fish BSS, with overfishing being the main factor. The ABC curve exhibited that Daya Bay was in a critical state of disturbance throughout the year. The spring, summer, and autumn were in severe disturbance, while the winter was in moderate disturbance.